Theoretical Assessment of Td-Dft Applied to a Ferrocene-Based Complex - Moya-Duran, S; Moya-Duran, S; Cardenas-Jiron, G; Yanez-Sanchez, M (Elsevier B.V., 2017)
We present a theoretical study of the electronic absorption spectrum of the 2-ferrocenyl-1,8-naphthyridine (FcNP) complex using the time-dependent density functional theory (TD-DFT) approach. The calculations were carried out at the DFT/LANL2DZ(Fe)/6-31++G(d) level of theory with nine DFT functionals of the type GGA (PBE, B97D), HGGA (B3LYP, PBE0), HMGGA (M05, M06) and range-separated (wB97XD, CAM-B3LYP, LC-wPBE) in the condensed phase (CH2Cl2). The experimental spectrum for FcNP presents three electronic absorption bands (A, B, C) in the UV region and one band (D) in the visible region. We found that there is no unique functional that reproduces the entire electronic spectrum. GGA and LC-wPBE functionals predict large errors (up to 0.57 eV) for the UV bands. On the contrary, HGGA (PBE0), HMGGA (M05, M06) and range-separated (wB97XD, CAM-B3LYP) functionals give small errors for these bands, 0.18, 0.12 and 0.25 eV, respectively. Band D is well described by all the functionals with errors up to 0.26 eV, except by the M05 and M06 functionals, which fail in this region with significant errors (0.52 and 0.56 eV). The analysis of the excitation energies shows that the PBE0, wB97XD and CAM-B3LYP functionals predict the best agreement with the experimental data. The two stronger bands (A, B) in the UV region are assigned to a ligand–ligand charge transfer (L-LCT) that involves the cyclopentadienyl rings (Cp) and the naphthyridine fragment (NP), and then associated with π → π∗ electronic transitions. The two weaker bands (C, D) are assigned to a charge transfer from ligand (Cp) to metal (Fe)-ligand (NP) (L-MLCT) which is mainly addressed through the dxy and dz2 atomic orbitals, respectively. No charge transfer is observed between metal and NP ligand. It was shown that the theoretical methods used for understanding the electronic absorption properties of FcNP were adequate because the results showed an excellent agreement with experimental ones. © 2017 Elsevier B.V.